ANTARA KEBEBASAN BEREKSPRESI DAN PERLINDUNGAN TERHADAP HATE SPEECH: STUDI KASUS PRIMA GAIDA JOURNALITA TAHUN 2017 - Theresia Bernadete Omi Diaz; Fadil Mas'ud; Adelheid Timu; Yohanes Lengari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Freedom of expression is one of the main pillars in the enforcement of civil and political rights as stipulated in the International Covenant on Civil and Political Rights (ICCPR) and guaranteed by the 1945 Constitution of the Republic of Indonesia. This article aims to analyze in depth the relationship between civil and political rights and freedom of expression on social media, as well as the legal limits on hate speech. This study uses a qualitative approach through a literature review of national legislation, international human rights instruments, and the results of research and reports from relevant institutions. The results of the study show that freedom of expression in Indonesia still faces a dilemma between the protection of individual rights and the enforcement of social order. The ITE Law, National Police Chief Regulation No. 8 of 2013, and articles of the Criminal Code have become the legal basis for prosecuting hate speech, but their implementation often raises interpretative issues that have the potential to limit the space for digital democracy. Therefore, a balanced approach is needed through strengthening digital literacy, education on social media ethics, and reformulating legal policies that emphasize the distinction between constructive criticism and hate speech. These efforts are expected to create a democratic, civilized digital ecosystem that respects human rights within the framework of civil and political rights